Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai pada Satuan Polisi Pamong Praja Karawang - Risma Sri Mardini; Sari Marliani; July Yuliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research aims to determine the influence of the work environment and work discipline on employee performance. The research was carried out at the Karawang Civil Service Police Unit office located at Jl. A. Yani No.70, Nagasari, Kab. Karawang. The research method is quantitative descriptive verification with multiple linear regression analysis using SPSS V.25 software. The population of the Karawang Civil Service Police Unit is 110 employees and the sample is 86 employees using the Slovin formula. Based on the research results, it can be concluded, 1) work environment with a score of 249 criteria is quite good, 2) work discipline with a score of 240 criteria is quite good, 3) employee performance with a score of 259 criteria is quite good, 4) work environment partially has a very significant positive effect on sig value is 0.000 < 0.05 and tcount is 5.920 > 1.988, 5) work discipline has a significant positive effect with sig value 0.001 < 0.05 and tcount is 3.511 > 1.988 on employee performance in the Karawang Civil Service Police Unit, 6) work environment and work discipline has a very significant simultaneous effect with a sig value of 0.000 < 0.05 and fcount 50.820 > ftable 3.107 on the performance of the Karawang Civil Service Police Unit employees. The determination value is 0.550 or 55%, while the remaining 0.450 or 45% is another variable that was not examined in this study. If the agency creates a comfortable work environment, employees will be more disciplined in their work so that it can influence employee performance to improve in the future in the Karawang Civil Service Police Unit.